Moderasi Beragama dalam Pendidikan Agama Islam di Era Society 5.0 - Munawir Munawir; Muhammad Alfin Nashri As; Khoirul Huda; Muhammad Nuril Mubin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to explore the significance of religious moderation in the digital age and examine the strategic role of Islamic Religious Education in instilling values of balance, tolerance, and moderate religious attitudes in the Society 5.0 era. Indonesia’s unique social character, marked by diversity in religion, language, ethnicity, and culture within the framework of Pancasila, necessitates systematic efforts to establish religious moderation as a guiding filter in national life. This study applies a qualitative approach using library research methods by reviewing relevant literature, including academic books, scholarly articles, and other credible sources. The findings reveal that education plays a vital role in nurturing the spirit of religious moderation by strengthening values of tolerance, balance, and respect for diversity. Islamic Religious Education serves as a strategic tool to cultivate a moderate understanding of religion grounded in inclusive Islamic principles, thereby fostering a peaceful, safe, and harmonious society amid the dynamics of digital transformation.